Desulfurization adsorbent and preparation method and application thereof

By using the carrier, the large -hole SB powder, silicon oxide, and potassium modified large pores are integrated to be compounded by thin water aluminum and stone, combined with decarcus adsorbents such as zinc, nickel, cobalt, and copper, solving the heavy quality among the existing technologies The problem of poor oil desulfurization effect has achieved high -efficiency and stable heavy oil depth desulfurization.

CN116408043BActive Publication Date: 2025-01-28PETROCHINA CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202111646210.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-01-28
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

The existing desulfurization agents have limited effects in the desulfurization treatment of heavy oils, and their desulfurization activity, stability and service life are insufficient.

Method used

The carrier is composed of small -hole SB powder, silicon and potassium modified large holes. It is integrated with a thin water aluminum and aluminum stone. It combines metal components such as zinc, nickel, cobalt, and copper to achieve efficient desulfurization through multiple steps.

Benefits of technology

It has significantly improved the desulfurization rate, a wide range of applications, especially suitable for deep desulfurization of heavy oil, and the adsorbent has good mechanical properties and activity stability, and has a long service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003443936150000221
    Figure BDA0003443936150000221
  • Figure HDA0003443936160000011
    Figure HDA0003443936160000011
  • Figure HDA0003443936160000021
    Figure HDA0003443936160000021
Patent Text Reader

Abstract

The present invention provides a desulfurization adsorbent and a preparation method and application thereof. The desulfurization adsorbent comprises a carrier, a first metal component and a second metal component. The carrier is compounded from raw materials including small-pore SB powder, silicon oxide and potassium-modified macroporous pseudo-boehmite, wherein the pore volume of the small-pore SB powder is not greater than 0.6 mL / g, and the pore volume of the potassium-modified macroporous pseudo-boehmite is not less than 0.8 mL / g; the first metal component comprises zinc and nickel, and the second metal component comprises cobalt and / or copper. The desulfurization adsorbent of the present invention has the advantages of high strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a desulfurization adsorbent and a preparation method and application thereof, belonging to the field of desulfurization of sulfur-containing oil products. Background Art

[0002] With the improvement of environmental protection requirements, low-sulfur clean oil products have received extensive attention. For example, traditional marine fuel oil is mainly high-sulfur fuel oil, which produces pollutants such as sulfide and sulfur oxide during its combustion. In order to control pollution, the International Maritime Organization (IMO) announced that it will enforce new sulfur emission restrictions from January 1, 2020. Therefore, it is urgent to reduce the sulfur content in fuel oil and other oil products and develop low-sulfur clean oil products. In addition, desulfurization of heavy oil such as residual oil and converting it into low-sulfur clean oil products as a blending component of fuel oil and other oil products is an important way to achieve efficient utilization of heavy oil.

[0003] Hydrodesulfurization and adsorption desulfurization are common means to achieve the purpose of oil desulfurization, for example, patent document CN109420507A discloses a hydrodesulfurization catalyst containing a macroporous alumina carrier, including 82-95wt% of a macroporous alumina carrier, the carrier uses styrene-butadiene rubber emulsion as a pore-enlarging agent, the molybdenum oxide content is 2-14wt%, and the cobalt oxide content is 1-5wt%, which is used for selective hydrodesulfurization of catalytic cracking gasoline; CN104549131A discloses an adsorption desulfurization aid, including a carrier and a metal oxide component loaded on the carrier, the carrier is a mixture of aluminum oxide and silicon oxide, and the metal oxide component is selected from sodium oxide, potassium oxide, magnesium oxide, calcium oxide, titanium oxide, vanadium oxide, One or more of chromium oxide, manganese oxide, iron oxide, copper oxide, zinc oxide, zirconium oxide, lanthanum oxide, cerium oxide, praseodymium oxide and neodymium oxide. The additive needs to be used in combination with a desulfurization adsorbent for desulfurization of catalytic cracking gasoline. CN106824068A discloses a bamboo-derived porous biomass fuel oil highly selective adsorption desulfurizer, which is obtained by chemical activation carbonization and concentrated nitric acid oxidation and is used for selective adsorption desulfurization of fuel oil. CN101804325A discloses a method for preparing a modified activated carbon adsorption desulfurizer, wherein the activated carbon is placed in an oxidant solution for oxidation modification, and then placed in a metal salt solution, a transition metal is loaded on the activated carbon, and a desulfurizer is obtained after drying. The transition metal includes copper, silver, and nickel. , zinc or cerium, the desulfurizer is used for desulfurization treatment under non-hydrogen conditions; CN104511286A discloses a desulfurization catalyst, which is composed of a silicon oxide source, a non-aluminum oxide, zinc oxide, lead oxide, and an active metal, the non-aluminum oxide is one of zirconium dioxide, titanium dioxide, and tin dioxide, and the active metal is one of cobalt, nickel, iron, and manganese. The desulfurization catalyst is used for desulfurization treatment of cracked gasoline and diesel fuel; CN104028208A discloses a gasoline highly selective desulfurization adsorbent, which uses activated carbon as a carrier, zinc oxide and nickel oxide as metal active components, so that the interaction between the carrier and the metal active components is weakened, ensuring that the adsorbent has sufficient and effective active components and improving the activity The utilization rate of the active components is improved, and the regeneration performance is improved. The desulfurization adsorbent is used for the selective desulfurization of gasoline; CN104028217A discloses a gasoline highly selective adsorption desulfurizer, which is composed of nickel oxide, zinc oxide and carbon aerogel and is used for the selective desulfurization of gasoline; CN105617984A discloses a gasoline desulfurization adsorbent and a preparation method thereof, wherein the active components, a carrier and water are evenly mixed and then molded, and then dried and roasted to obtain the adsorption desulfurizer, wherein the active components contain zinc oxide, nickel oxide, nickel carbonate, calcium oxide, magnesium oxide, potassium chloride and potassium sulfite, and the carrier contains silicon oxide, aluminum oxide and SBA-15. The adsorbent is mainly used for gasoline adsorption desulfurization, and the adsorption desulfurizer is used for gasoline adsorption desulfurization;CN108212077A discloses a gasoline adsorption desulfurization agent, comprising ethanol, attapulgite, zinc oxide, and triethylenediamine, for adsorption desulfurization of gasoline. ;

[0004] Desulfurizer is an important factor affecting the desulfurization effect. Optimizing the structure and performance of desulfurizer is an effective means to improve the desulfurization effect. Although there have been studies and reports on desulfurizers such as hydrodesulfurizers and adsorption desulfurizers, on the one hand, the strength, desulfurization activity, stability and desulfurization efficiency of desulfurizers at this stage need to be further improved. On the other hand, the current desulfurizers are mostly used for the desulfurization of light oils such as gasoline, kerosene and diesel, but have limited desulfurization effects on heavy oils. It is urgent to develop effective desulfurizers suitable for the desulfurization of heavy oils. Summary of the invention

[0005] The present invention provides a desulfurization adsorbent and a preparation method and application thereof, which has the advantages of high adsorbent strength, good stability and high desulfurization efficiency, and is particularly suitable for desulfurization treatment of heavy oil, effectively overcoming the defects of the prior art.

[0006] In one aspect of the present invention, a desulfurization adsorbent is provided, comprising a carrier, a first metal component and a second metal component, wherein the carrier is compounded from raw materials comprising small-pore SB powder, silicon oxide and potassium-modified macroporous pseudo-boehmite, wherein the pore volume of the small-pore SB powder is not greater than 0.6 mL / g, and the pore volume of the potassium-modified macroporous pseudo-boehmite is not less than 0.8 mL / g; the first metal component comprises zinc and nickel, and the second metal component comprises cobalt and / or copper.

[0007] According to one embodiment of the present invention, based on the oxide of the first metal component and the oxide of the second metal component, the following conditions are met: the mass of the first metal component accounts for 60% to 80% of the sum of the masses of the carrier and the first metal component; and / or the mass of nickel in the first metal component accounts for 3% to 13% of the sum of the masses of the carrier and the first metal component; and / or the mass of the second metal component accounts for 0.4% to 1% of the sum of the masses of the carrier and the first metal component.

[0008] According to one embodiment of the present invention, the pore volume of the small-pore SB powder is 0.4 mL / g to 0.6 mL / g, and the specific surface area is 180 m 2 / g~260m 2 / g, the peptization index is greater than 98%; and / or the pore volume of the potassium-modified macroporous pseudo-boehmite is 0.8mL / g to 1.2mL / g, and the specific surface area is 280m 2 / g~360m 2 / g; and / or, the mass ratio of the small-pore SB powder to the potassium-modified macroporous pseudo-boehmite is 1:(2-5); and / or, the ratio of the mass of the silicon oxide to the sum of the masses of the potassium-modified macroporous pseudo-boehmite and the small-pore SB powder is (0.1-0.4):1.

[0009] According to one embodiment of the present invention, the potassium-modified macroporous pseudo-boehmite is prepared according to a process comprising the following steps: a pseudo-boehmite raw material is impregnated with a second impregnation solution containing a potassium compound, and the pseudo-boehmite is obtained after drying and roasting; wherein the mass ratio of the second impregnation solution to the pseudo-boehmite raw material is (2-5):1; the potassium compound comprises at least one of potassium nitrate, potassium carbonate, potassium sulfate, and potassium chloride; the mass ratio of the potassium compound to the pseudo-boehmite raw material is (0.05-0.3):1, calculated as potassium oxide; the drying temperature is 80°C-120°C, and the roasting temperature is 450°C-550°C.

[0010] Another aspect of the present invention provides a method for preparing the above-mentioned desulfurization adsorbent, comprising: (I) adding inorganic acid and water to a mixture containing potassium-modified macroporous pseudo-boehmite, small-pore SB powder, silicon oxide, a binder, zinc oxide, and a nickel compound, and then sequentially performing molding, drying, and calcining to obtain an intermediate; (II) impregnating the intermediate with a first impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain an adsorbent precursor; (III) performing a first reduction treatment on the adsorbent precursor in an atmosphere containing hydrogen to obtain the desulfurization adsorbent.

[0011] According to one embodiment of the present invention, the binder comprises at least one of methyl cellulose, sodium carboxymethyl starch and sesbania powder; and / or, the mass of the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 2% to 6% of the sum of the mass of the potassium-modified macroporous pseudo-boehmite, small-pore SB powder, silicon oxide, zinc oxide and the nickel compound; and / or, the zinc oxide comprises nano zinc oxide powder with a particle size of not more than 100 nm; and / or, the ratio of the mass of the inorganic acid to the sum of the mass of the potassium-modified macroporous pseudo-boehmite and small-pore SB powder is (0.1 to 0.5):1; and / or, the calcination conditions in step (I) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, the calcination conditions in step (II) are: the calcination temperature is 400°C to 700°C, and the calcination time is 1h to 10h; and / or, in step (III), the volume space velocity of the hydrogen is 500h -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h.

[0012] In another aspect of the present invention, a method for desulfurization of sulfur-containing oil is provided, comprising: using the above-mentioned desulfurization adsorbent to desulfurize the sulfur-containing oil; or, preparing the desulfurization adsorbent according to the above-mentioned preparation method, and using the prepared desulfurization adsorbent to desulfurize the sulfur-containing oil.

[0013] According to one embodiment of the present invention, the temperature of the desulfurization treatment is 300°C to 550°C; and / or, the pressure of the desulfurization treatment is 0.5MPa to 10MPa; and / or, the feed space velocity of the sulfur-containing oil product is 0.1h -1 ~1.0h -1 ; and / or, the desulfurization treatment is carried out under a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):1.

[0014] According to one embodiment of the present invention, the method further comprises: obtaining a desulfurized oil product and a regenerated adsorbent after the desulfurization treatment; regenerating the regenerated adsorbent to obtain a regenerated adsorbent; and returning the regenerated adsorbent to the desulfurization treatment; wherein the regeneration treatment comprises: subjecting the regenerated adsorbent to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000h / min. -1 ~3000h -1 The temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5 MPa, and the time of the oxidation regeneration is 20h to 100h; the regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated adsorbent; wherein the volume space velocity of the hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300° C. to 500° C., the pressure of the second reduction treatment is 0 to 3 MPa, and the time of the second reduction treatment is 1 h to 6 h.

[0015] According to one embodiment of the present invention, the sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0016] The desulfurization adsorbent provided by the present invention has the advantages of good mechanical properties, long service life, good desulfurization activity, etc., can significantly improve the desulfurization rate, and has a wide range of applications, especially suitable for the desulfurization treatment of heavy oil, effectively removes sulfides such as thiophenes, realizes the deep desulfurization of sulfur-containing oil products such as heavy oil, improves the quality of the desulfurized oil products, and the desulfurized oil products can be used as clean gasoline blending components or other uses. Studies have shown that the breaking strength of the desulfurization adsorbent is as high as 40N or more, showing good mechanical properties, good structural stability, meeting the requirements of processes such as moving beds, and having a wide range of applications; the desulfurization rate of heavy oil is as high as more than 80%, and the desulfurization adsorbent can still achieve a good desulfurization rate (basically more than 80%) after being regenerated 1 to 35 times or even more times, showing good activity stability and long service life. In addition, the raw materials of the desulfurization adsorbent of the present invention are cheap and easy to obtain, and it also has the advantages of low cost, simple preparation process, and simple desulfurization process using the desulfurization adsorbent, mild conditions, and high efficiency, which is of great significance for practical industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 XRD spectra of the adsorbent precursors during the preparation of fresh desulfurization adsorbents S1, S2, D4, and D5 (the abscissa is the 2θ angle (Theta), and the ordinate is the peak intensity (intensity));

[0018] Figure 2 This is the XRD spectrum of the regenerated adsorbent precursor during the regeneration process of the regenerated adsorbent produced after desulfurization treatment of S1, S2, D4, and D5. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only descriptions of the principles and features of the present invention. The examples given are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the present invention, terms such as "first" and "second" are only used for descriptive purposes, such as distinguishing between components to more clearly illustrate / explain the technical solution, and cannot be understood as indicating or implying the number of technical features indicated or the order of substantial significance.

[0020] The desulfurization adsorbent of the present invention comprises: a carrier, a first metal component and a second metal component, wherein the carrier is compounded from raw materials comprising small-pore SB powder, silicon oxide and potassium-modified macroporous pseudo-boehmite, wherein the pore volume of the small-pore SB powder is not greater than 0.6 mL / g, and the pore volume of the potassium-modified macroporous pseudo-boehmite is not less than 0.8 mL / g; the first metal component comprises zinc and nickel, and the second metal component comprises cobalt and / or copper.

[0021] After research and analysis, the inventor believes that, in the desulfurization adsorbent composition system of the present invention, the first metal component serves as the main active component for sulfur adsorption / absorption. During the desulfurization treatment of the oil product, the sulfur element in the oil product is captured by the nickel component in the adsorbent to form nickel sulfide. The nickel sulfide reacts with the zinc component to form zinc sulfide. The second metal component, as an active metal, can promote the sulfur transfer and other processes. Thus, through multi-step coordinated reactions, the sulfur component in the oil product is adsorbed in the desulfurization adsorbent in the form of metal sulfides such as zinc sulfide, thereby achieving the purpose of desulfurization.

[0022] Generally speaking, when a desulfurization adsorbent using a conventional alumina-based carrier and zinc oxide and nickel as the main adsorption active components is used for adsorption desulfurization of heavy oil, there will be at least the following problems: First, due to the inherent properties of ZnO as the main adsorption component, the strength of the adsorbent is poor; second, there is a strong interaction between the adsorption active component (such as ZnO) and the carrier Al2O3, and zinc-aluminum spinel is easily formed during the adsorption desulfurization reaction, adsorbent regeneration and other cyclic processes, causing some adsorption active components such as ZnO to lose the ability to desulfurize and store sulfur, thereby gradually deactivating the desulfurization adsorbent, and at the same time reducing the strength of the adsorbent, affecting the desulfurization performance and service life of the adsorbent. Third, ZnO is gradually converted into ZnS, which also causes the adsorbent to gradually lose its desulfurization ability and needs to be regenerated. However, due to the high sulfur content in heavy oil (usually higher than 1wt%), the single-pass operation time of the adsorbent is short and the regeneration frequency is high. The desulfurization performance of the regenerated adsorbent is poor, resulting in a short overall service life of the adsorbent.

[0023] According to the research of the present invention, a carrier is formed by compounding small-pore SB powder, silicon oxide and potassium-modified macroporous pseudo-boehmite, and the first metal component and the second metal component are matched to form a desulfurization adsorbent, which can effectively solve the above problems. The inventor believes through research and analysis that the carrier formed by compounding small-pore SB powder, potassium-modified macroporous pseudo-boehmite and silicon oxide can improve the mechanical properties such as the fracture strength of the desulfurization adsorbent (the crushing strength is as high as 40N or more), ensure its structural stability, and at the same time, the potassium therein can react with zinc oxide to promote the transfer of sulfur to zinc oxide during the desulfurization process. The reaction converts more zinc oxide into active zinc oxide, thereby improving the sulfur storage capacity of the desulfurization adsorbent, that is, improving the sulfur capacity of the desulfurization adsorbent. Studies have shown that the sulfur capacity of the desulfurization adsorbent of the present invention can be increased from no more than 5.5% when potassium-modified macroporous pseudo-boehmite is not used to more than 7.5%; the addition of silicon oxide can improve the dispersion of active components in the desulfurization adsorbent, weaken the interaction between aluminum oxide and zinc oxide, and inhibit the formation of zinc aluminum spinel, thereby further ensuring the strength and stability of the adsorbent, facilitating its recycling and regeneration, and improving its service life. Therefore, the desulfurization adsorbent of the present invention has good adsorption desulfurization activity, as well as desulfurization activity stability, structural stability and other properties.

[0024] In the present invention, potassium-modified macroporous pseudo-boehmite can be obtained by loading potassium element on a pseudo-boehmite raw material, and the pseudo-boehmite raw material used is generally a macroporous pseudo-boehmite material with a large pore volume. In specific implementation, potassium element can be loaded on the pseudo-boehmite raw material by an impregnation method to obtain potassium-modified macroporous pseudo-boehmite. For example, in some preferred embodiments, potassium-modified macroporous pseudo-boehmite is obtained according to a process including the following steps: the pseudo-boehmite raw material is impregnated with a second impregnation liquid containing a potassium compound, and after drying and roasting, potassium-modified macroporous pseudo-boehmite is obtained. In specific implementation, the impregnation can be performed by an equal volume impregnation method.

[0025] Wherein, in terms of potassium oxide (i.e., K2O), the mass ratio of the potassium compound to the pseudo-boehmite raw material can be (0.05-0.5):1, for example, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1 or a range consisting of any two thereof, and the mass ratio of the second impregnating solution to the pseudo-boehmite raw material can be (2-5):1, for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or a range consisting of any two thereof, preferably (3-4):1; the potassium compound can specifically include potassium salt, preferably including at least one of potassium nitrate, potassium carbonate, potassium sulfate, and potassium chloride.

[0026] In addition, the impregnation process of the pseudo-boehmite raw material with the second impregnation liquid can be carried out at room temperature, and the impregnation time can be 1h to 5h, preferably 2h to 4h. After the impregnation is completed, the impregnation product can be filtered, washed and then dried. Among them, the drying temperature can be 80℃ to 120℃, such as 80℃, 90℃, 100℃, 110℃, 120℃ or the range of any two thereof, and the drying time is 6h to 10h; the roasting temperature is 450℃ to 550℃, such as 450℃, 480℃, 500℃, 520℃, 550℃ or the range of any two thereof, and the roasting time can be 2h to 5h.

[0027] In the present invention, the carrier is compounded from small-pore SB powder, silicon oxide, potassium-modified macroporous pseudo-boehmite and other raw materials. To further optimize the adsorbent performance, the pore volume of the small-pore SB powder can be 0.4 mL / g to 0.6 mL / g, such as 0.4 mL / g, 0.5 mL / g, 0.6 mL / g, etc., and the specific surface area is 180 m 2 / g~260m 2 / g, for example 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g or any two thereof, and its peptization index is greater than 98%.

[0028] In addition, the pore volume of potassium-modified macroporous pseudo-boehmite can be 0.8 mL / g to 1.2 mL / g, such as 0.8 mL / g, 0.9 mL / g, 1 mL / g, 1.1 mL / g, 1.2 mL / g or any two thereof, and the specific surface area is 280 m 2 / g~360m 2 / g, for example 280m 2 / g, 290m 2 / g、300m 2 / g, 310m 2 / g, 320m 2 / g, 330m 2 / g, 340m 2 / g, 350m 2 / g, 360m 2 / g or a range consisting of any two thereof.

[0029] After further study, the mass ratio of small-pore SB powder to potassium-modified large-pore pseudo-boehmite can be 1:(2-5), for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or a range consisting of any two of them.

[0030] In some embodiments, the ratio of the mass of silicon oxide to the sum of the mass of potassium-modified macroporous pseudo-boehmite and small-pore SB powder is (0.1-0.4):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1 or a range consisting of any two thereof.

[0031] In the above-mentioned desulfurization adsorbent, the mass percentage of the first metal component serving as the sulfur absorption unit is generally not lower than (i.e. equal to or greater than) the mass percentage of the carrier. In some preferred embodiments, calculated as the oxide of the first metal component, the mass of the first metal component accounts for 60% to 80% of the sum of the masses of the carrier and the first metal component, for example, 60%, 65%, 70%, 75%, 80% or the range of any two thereof, and the mass of the carrier accounts for 20% to 40% of the sum of the masses of the carrier and the first metal component, for example, 20%, 25%, 30%, 35%, 40% or the range of any two thereof.

[0032] In general, the mass percentage of zinc in the first metal component is preferably higher than the mass percentage of nickel, calculated as the oxide of the first metal component. In some embodiments, the mass of nickel in the first metal component accounts for 3% to 13% of the sum of the mass of the support and the first metal component, such as 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13% or a range consisting of any two thereof, calculated as the oxide of the first metal component.

[0033] In some embodiments, the mass of the second metal component, calculated as the oxide of the first metal component and the oxide of the second metal component, accounts for 0.4% to 1% of the sum of the masses of the support and the first metal component, for example, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or a range consisting of any two thereof.

[0034] In the above-mentioned desulfurization adsorbent, the first metal component and the second metal component are loaded on a carrier. Generally, most of the metal components exist in the form of oxides (such as zinc exists in the form of zinc oxide), wherein at least part of the nickel can be present in a reduced state (i.e., in the form of nickel element). In specific implementation, compounds of each metal component (such as metal oxides and / or metal salts, etc.) can be used to load each metal component on a carrier by an impregnation method. After the loading of each metal component is completed, the obtained adsorbent precursor is subjected to a first reduction treatment in an atmosphere containing hydrogen, so that the nickel component therein is at least partially reduced to nickel element, thereby obtaining a desulfurization adsorbent and improving its desulfurization activity.

[0035] The above-mentioned carrier can be specifically prepared by compounding raw materials containing potassium-modified macroporous pseudo-boehmite, small-pore SB powder, silicon oxide and a binder, and its preparation process can include: mixing potassium-modified macroporous pseudo-boehmite, small-pore SB powder, silicon oxide, a binder with an inorganic acid and water, and then drying and calcining to form a carrier. The metal component can be introduced during the preparation process of the carrier, or the metal component can be impregnated after the carrier is prepared.

[0036] In a preferred embodiment of the present invention, the preparation method of the above-mentioned desulfurization adsorbent includes: (I) adding inorganic acid and water to a mixture containing potassium-modified macroporous pseudo-boehmite, small-pore SB powder, silicon oxide, a binder, zinc oxide, and a nickel compound, and then sequentially forming, drying, and calcining to obtain an intermediate; (II) using a first impregnation solution containing a compound of a second metal component to impregnate the intermediate, and after drying and calcining the impregnation product, an adsorbent precursor is obtained; (III) the adsorbent precursor is subjected to a first reduction treatment in an atmosphere containing hydrogen to obtain a desulfurization adsorbent.

[0037] In the above preparation process, the raw materials of the first metal component (zinc oxide and nickel compound) and the carrier raw materials (potassium-modified macroporous pseudo-boehmite, small-pore SB powder, silicon oxide, binder) are first mixed and formed, and then the second metal component is impregnated, which can improve the strength and desulfurization activity of the prepared desulfurization adsorbent. The inventors have studied and analyzed that, in the above-mentioned preparation process, after the drying, calcination and other treatments of steps (I) to (II), potassium-modified macroporous pseudo-boehmite, small-pore SB powder and silicon oxide are compounded to form a carrier, and the binder gradually volatilizes during the calcination process, thereby forming a pore structure in the obtained adsorbent, and the nickel compound and the compound of the second metal component are basically converted into metal oxides; after the first reduction treatment of step (III), the nickel therein can be basically present in a reduced state, while other metal components (such as zinc and the second metal component) are usually still present in the form of metal oxides, thereby a desulfurization adsorbent with suitable composition and structure can be prepared, which is suitable for the desulfurization treatment of heavy oil, and can exhibit good adsorption desulfurization activity, stability and mechanical properties, thereby improving the desulfurization rate and service life.

[0038] Specifically, in the above preparation process, the first metal component compound includes zinc oxide and nickel compound, and the second metal component compound includes cobalt compound and / or copper compound. In general, the content of each metal component in the prepared desulfurization adsorbent can be regulated by the amount of raw materials such as each metal component compound, and the amount of each raw material is as follows: based on the oxide of each metal component (such as nickel compound based on nickel oxide, cobalt compound based on cobalt oxide, and copper compound based on copper oxide), the mass of the first metal component compound accounts for 60% to 80% of the sum of the mass of the carrier and the first metal component compound, the mass of the nickel compound accounts for 3% to 13% of the sum of the mass of the carrier and the first metal component compound, the mass of the second metal component compound accounts for 0.4% to 1% of the sum of the mass of the carrier and the first metal component compound, the mass ratio of small-pore SB powder to potassium-modified macroporous pseudo-boehmite is 1: (2 to 5), and the mass ratio of silicon oxide to the sum of the mass of potassium-modified macroporous pseudo-boehmite and small-pore SB powder is (0.1 to 0.4): 1.

[0039] In step (I), the mixture can be a wet mixture, a paste mixture, a kneaded body or a slurry, etc., and the molding process can be oil-ammonia column molding, oil-water column molding, oil column molding, rolling ball molding or extrusion ball molding, etc., preferably extrusion ball molding, wherein the amount of water used can be convenient for molding, for example, it can meet the extrusion ball molding, and there is no particular limitation on this. Through the above molding process, the intermediate formed can be spherical and / or toothed ball-shaped, and the particle diameter of the intermediate is preferably 1.5mm to 3mm, for example, 1.5mm, 2mm, 2.5mm, 3mm or the range composed of any two thereof.

[0040] In step (I), the nickel compound may include, in particular, a soluble nickel compound (e.g., a water-soluble nickel compound), such as a soluble nickel salt, preferably nickel nitrate and / or nickel acetate. The soluble nickel salt may be in the form of a hydrate without or with water of crystallization, and the present invention is not particularly limited to this.

[0041] In step (I), the zinc oxide may include nano-sized particles of zinc oxide, preferably nano zinc oxide powder with a particle size of no more than 100 nm. In specific implementation, the purity of the zinc oxide used is greater than 96%.

[0042] In step (I), the binder may include at least one of methylcellulose, sodium carboxymethyl starch, and sesbania powder. In addition, the amount of the binder can generally be controlled as follows: the mass of the nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 2% to 6% of the sum of the mass of potassium-modified macroporous pseudo-boehmite, microporous SB powder, silicon oxide, zinc oxide and the nickel compound, for example, 2%, 3%, 4%, 5%, 6% or a range consisting of any two of them.

[0043] In some embodiments, in step (I), the ratio of the mass of the inorganic acid to the sum of the mass of the potassium-modified macroporous pseudo-boehmite and the small-pore SB powder is (0.1-0.5):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1 or any two of them. It should be noted that the ratio of the mass of the inorganic acid to the sum of the mass of the potassium-modified macroporous pseudo-boehmite and the small-pore SB powder is calculated based on the inorganic acid without solvents such as water. In specific implementation, inorganic acid solutions of different concentrations may be used, and the mass of the inorganic acid therein can be converted according to its concentration, and the ratio of the mass of the inorganic acid (non-solution) to the sum of the mass of the potassium-modified macroporous pseudo-boehmite and the small-pore SB powder is controlled to be (0.1-0.5):1. Preferably, the inorganic acid includes nitric acid.

[0044] In step (II), the first impregnation solution may be a solution or a suspension. Preferably, the compound of the second metal component includes a soluble compound of the second metal component (generally a water-soluble compound). The first impregnation solution is a solution prepared by dissolving the soluble compound of the second metal component in water. The compound of the second metal component may specifically include a soluble salt of the second metal component (i.e., a soluble salt of cobalt and / or a soluble salt of copper), preferably a nitrate of the second metal component (i.e., cobalt nitrate and / or copper nitrate).

[0045] In specific implementation, in step (II), the impregnation can be carried out by an equal volume impregnation method. In some embodiments, in step (II), the impregnation temperature is 20°C to 90°C, for example, 20°C, 30°C, 40°C, 50°C, 60°C, 65°C, 70°C, 80°C, 90°C or any two thereof in the range, preferably 40 to 65°C, the impregnation time is 1h to 24h, for example, 1h, 5h, 10h, 15h, 20h, 24h or any two thereof in the range, preferably 6h to 12h; the mass ratio of the first impregnation liquid to the intermediate is (1 to 4): 1, for example, 1: 1, 2: 1, 1.5: 1, 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1 or any two thereof in the range.

[0046] Optionally, the drying process in step (I) and step (II) independently comprises: first drying at 20°C to 30°C (such as room temperature) for 12h to 48h, then drying at 60°C to 120°C (preferably 80°C to 110°C) for 3h to 24h (preferably 6h to 10h), and then calcining the obtained dried product. The drying temperature, drying time and other conditions in step (I) and step (II) may be the same or different.

[0047] In addition, the calcination conditions in step (I) and step (II) can be independently: the calcination temperature is 400°C to 700°C, such as 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C or any two of them in the range, preferably 450°C to 650°C, and the calcination time is 1h to 10h, such as 1h, 3h, 5h, 7h, 10h or any two of them in the range, preferably 3h to 5h. Wherein, the calcination temperature, calcination time and other conditions in step (I) and step (II) can be the same or different.

[0048] In step (III), hydrogen can be introduced into the system to contact the adsorbent precursor with hydrogen to perform the first reduction treatment. The volume space velocity of hydrogen can be 500h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 、2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, in step (III), the volume fraction of hydrogen in the atmosphere containing hydrogen is 50% to 100%, for example, 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, and the remainder is, for example, an inert gas.

[0049] In step (III), the temperature of the first reduction treatment process can be 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof, preferably 350°C to 450°C, the pressure of the first reduction treatment process is 0 to 3MPa, for example, 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or a range consisting of any two thereof, preferably 0.5 to 1.5MPa, and the time of the first reduction treatment is 1h to 6h, for example, 1h, 2h, 3h, 4h, 5h, 6h or a range consisting of any two thereof, preferably 2h to 4h.

[0050] In the present invention, unless otherwise specified, the masses of raw materials such as modified macroporous pseudo-boehmite, microporous SB powder, silicon oxide, zinc oxide, etc. are all calculated on a dry basis.

[0051] In one embodiment of the present invention, a method for adsorption desulfurization of sulfur-containing oil is provided, comprising: using the above-mentioned desulfurization adsorbent to desulfurize the sulfur-containing oil; or, preparing the desulfurization adsorbent according to the above-mentioned preparation method, and using the prepared desulfurization adsorbent to desulfurize the sulfur-containing oil.

[0052] In some embodiments, the temperature of the desulfurization treatment can be 300°C to 550°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C or a range consisting of any two thereof, preferably 400-450°C; the pressure of the desulfurization treatment is 0.5MPa to 10MPa, for example, 0.5MPa, 1MPa, 2MPa, 3MPa, 4MPa, 5MPa, 6MPa, 7MPa, 8MPa, 9MPa, 10MPa or a range consisting of any two thereof, preferably 3MPa to 7MPa; the feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 , for example 0.1h -1 、0.3h -1 , 0.5h -1 , 0.8h -1 , 1h -1 Or a range consisting of any two of them.

[0053] In some embodiments, the desulfurization treatment is carried out in a hydrogen atmosphere, that is, the sulfur-containing oil and the desulfurization adsorbent are contacted and reacted in a hydrogen atmosphere to carry out the desulfurization treatment. The volume ratio of hydrogen to the sulfur-containing oil (hydrogen-to-oil volume ratio) is (100-800):1, such as 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1 or a range consisting of any two of them.

[0054] In some embodiments, the above desulfurization process further includes: obtaining desulfurized oil and regenerated adsorbent after desulfurization treatment; regenerating the regenerated adsorbent to obtain regenerated adsorbent; and returning the regenerated adsorbent for desulfurization treatment.

[0055] The regeneration process comprises: subjecting the regenerated adsorbent to oxidation regeneration in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or a range consisting of any two of them, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , for example 1000h -1 、1300h -1 、1500h -1 , 1800h -1 、2000h-1 , 2300h -1 、2500h -1 、2800h -1 、3000h -1 or a range consisting of any two thereof; the temperature of the oxidation regeneration is 300°C to 500°C, for example, 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof; the pressure of the oxidation regeneration is 0 to 0.5 MPa; the time of the oxidation regeneration is 20h to 100h; the regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated adsorbent; wherein the temperature of the second reduction treatment ... 0℃, 450℃, 500℃ or any two of them in the range, preferably 350~450℃, the pressure of the second reduction treatment is 0~3MPa, for example 0MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, 2.5MPa, 3MPa or any two of them in the range, preferably 0.5~1.5MPa, the time of the second reduction treatment is 1h~6h, for example 1h, 2h, 3h, 4h, 5h, 6h or any two of them in the range, preferably 2h~4h. In the present invention, unless otherwise specified, the pressures are all gauge pressures.

[0056] In a specific implementation, hydrogen can be introduced into the system to contact the regenerated adsorbent precursor with hydrogen to perform the second reduction treatment. The volume space velocity of hydrogen can be 500 h -1 ~4000h -1 , for example 500h -1 、1000h -1 、1500h -1 、2000h -1 、2500h -1 、3000h -1 、3500h -1 , 4000h -1 Or any two of them, preferably 1500h -1 ~3000h -1 Generally, during the second reduction treatment, the volume fraction of hydrogen in the hydrogen-containing atmosphere is 10% to 100%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100% or any two thereof, preferably 60% to 100%, and the remainder may be an inert gas or oil gas such as methane.

[0057] Specifically, the above desulfurization treatment is carried out in a reactor, and the reactor may include a fixed bed reactor and / or a moving bed reactor. Taking the fixed bed reactor as an example, in specific implementation, the desulfurization adsorbent may be loaded in the fixed bed reactor, and then the sulfur-containing oil product enters the fixed bed reactor, contacts and reacts with the desulfurization adsorbent therein, and obtains the desulfurized oil product and the regenerated adsorbent respectively; after the regenerated adsorbent is subjected to the above regeneration treatment, it is returned to the fixed bed reactor to form a cycle.

[0058] In the present invention, the above-mentioned desulfurization adsorbent can be used to remove small molecular sulfides and macromolecular sulfides in sulfur-containing oil products, and has a wide range of applications. Generally, the sulfides in the above-mentioned sulfur-containing oil products include at least one of carbon oxysulfide, carbon disulfide, mercaptan, hydrogen sulfide, and thiophene compounds, but are not limited thereto. For example, thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene. The present invention can efficiently remove these sulfides in sulfur-containing oil products, especially macromolecular sulfides such as thiophenes, achieve deep desulfurization of sulfur-containing oil products, and reduce the total sulfur content of desulfurized oil products. In some specific embodiments, the above-mentioned sulfur-containing oil products include heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

[0059] Generally speaking, the equivalent double bond value (DBE) of sulfides in heavy oil is distributed between 9 and 16. 22 -C 46 , mainly large molecular sulfides such as benzothiophene, dibenzothiophene, and benzonaphthiophene, which are difficult to remove, and the asphaltene and colloid particles in the heavy oil are large, which can easily block the catalyst pores and cause catalyst deactivation and other problems. The desulfurization adsorbent of the present invention can efficiently remove sulfides in heavy oil, and has good activity and stability, can be regenerated and used multiple times, and maintain good desulfurization efficiency.

[0060] In the present invention, the above-mentioned desulfurization adsorbent is used to desulfurize sulfur-containing oil products, and efficient desulfurization can also be achieved for sulfur-containing oil products with high sulfur content (such as the above-mentioned heavy oil). Taking heavy oil with a sulfur content of about 2.8wt% (such as vacuum residue) as an example, through the above-mentioned desulfurization process, the desulfurization rate can reach more than 80%.

[0061] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] In the following embodiments, the relevant performance testing process is as follows:

[0063] (1) With reference to the standard "SH / T 0689-2000", the total sulfur content in the liquid oil sample was determined by ultraviolet fluorescence / chemiluminescence method using the American photonLAB total sulfur and total nitrogen analyzer at a temperature of 1000°C, argon gas of 30psi, and oxygen of 10psi. According to this method, the mass percentage of total sulfur in the heavy oil feedstock x0 and the mass percentage of total sulfur in the desulfurized oil product x1 were determined respectively, and the desulfurization rate w was calculated according to w=(x0-x1) / x0;

[0064] (2) A universal automatic strength tester is used to measure the mechanical strength of the molded particles (such as S1 to S6, D1 to D6 below). The instrument range is 0 to 500 N, and the accuracy is 0.1 N. The measurement process is as follows: a single sample is placed between two rigid platforms, one of which remains stationary and the other moves axially downward at a very low speed to produce extrusion friction on the particles. The fracture strength (or crushing strength) is determined as the maximum load measured before the particles break. According to this process, 50 regular particles are selected for each sample to perform a crushing strength test, so as to obtain representative mechanical properties.

[0065] (3) The crystal structure of each adsorbent sample was characterized by X-ray diffraction (XRD) analysis. Specifically, the XRD analysis was performed using a Rigaku D / max 2200PC X-ray powder diffractometer under the conditions of Cu target, graphite monochromator, scanning speed of 10 degrees / min, scanning step of 0.02 degrees, voltage of 40 kV, and current of 20 mA. The intensity and position of the diffraction peaks in the measured XRD spectrum were qualitatively analyzed to determine the composition of the adsorbent (including the type of substance, structure, crystalline state, and state of existence of elements, etc.).

[0066] In the following examples and comparative examples, the small-pore SB powder was purchased from Suzhou Baird New Material Technology Co., Ltd., model DB03, and the pore volume of the small-pore SB powder was 0.486 mL / g and the specific surface area was 226 m 2 / g, the peptization index is greater than 98%; the macroporous pseudo-boehmite was purchased from Zibo Jiarun Chemical Co., Ltd., model JR-G-03; other reagents were purchased from Aladdin Reagent Network; the zinc oxide used was nano zinc oxide powder with a particle size not greater than 100nm.

[0067] In the following examples, the potassium-modified macroporous pseudo-boehmite was prepared according to the following process:

[0068] 1. Weigh 215g of potassium nitrate, add 2785g of deionized water to form a solution (i.e., the second impregnation solution), add 1000g of macroporous pseudo-boehmite raw material (calculated on a dry basis) to the solution, and then impregnate and modify for 3h under stirring conditions. After filtering and washing the impregnated product for multiple times, dry it at 100°C for 8h, and then calcine it at 500°C for 3h to obtain potassium-modified macroporous pseudo-boehmite I. After testing, the pore volume of the potassium-modified macroporous pseudo-boehmite I is 1.04mL / g, and the specific surface area is 328m 2 / g.

[0069] 2. Weigh 430g of potassium nitrate, add 3570g of deionized water to make a solution, then add 1000g of macroporous pseudo-boehmite raw material (calculated on dry basis) to the solution, then impregnate and modify for 3h under stirring conditions, filter and wash the impregnated product several times, dry it at 100℃ for 8h, and then calcine it at 500℃ for 3h to obtain potassium-modified macroporous pseudo-boehmite II; after testing, the pore volume of the potassium-modified macroporous pseudo-boehmite II is 1.16mL / g, and the specific surface area is 343mL / g.

[0070] Example 1

[0071] (1) 47 g of small-pore SB powder, 96 g of potassium-modified macroporous pseudo-boehmite I, 57 g of silicon oxide, 60 g of sesbania powder, 670 g of zinc oxide powder, and 432 g of nickel acetate tetrahydrate were mixed uniformly, 510 g of water and 71 g of nitric acid were added thereto, and after mixing uniformly, small balls with a particle diameter of 2 mm were squeezed out, and the small balls were naturally dried at room temperature for 24 hours; then dried at 100° C. for 8 hours, and then calcined at 550° C. for 4 hours to obtain a small ball intermediate;

[0072] (2) Weigh 23.5 g of copper nitrate, add 1000 g of water thereto to prepare a first impregnation solution, place the intermediate in the solution, and impregnate at 60° C. for 6 h; dry the obtained impregnation product at room temperature for 12 h, then dry at 110° C. for 6 h, and then calcine at 600° C. for 3 h to obtain an adsorbent precursor;

[0073] (3) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S1; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 2000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0074] Among them, the first metal component (zinc + nickel) and the second metal component (copper) are both calculated as oxides, the mass of the first metal component accounts for 80% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 13% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (copper oxide) accounts for 1% of the sum of the masses of the carrier and the first metal component.

[0075] Example 2

[0076] (1) 61 g of small-pore SB powder, 302 g of potassium-modified macroporous pseudo-boehmite II, 37 g of silicon oxide, 20 g of sesbania powder, 570 g of zinc oxide powder, and 117 g of nickel nitrate hexahydrate were mixed uniformly, 430 g of water and 36.3 g of nitric acid were added thereto, and after mixing uniformly, the mixture was extruded into small balls with a particle diameter of 2 mm (i.e., formed), and the small balls were naturally dried at room temperature for 12 hours; then dried at 80° C. for 10 hours, and then calcined at 450° C. for 5 hours to obtain a small ball intermediate;

[0077] (2) Weigh 9.8 g of cobalt nitrate (on a dry basis, excluding crystal water), add 3950 g of water thereto to prepare a first impregnation solution, place the intermediate in the first impregnation solution, impregnate at 50° C. for 10 h, and naturally dry the obtained impregnation product at room temperature for 18 h, then dry at 90° C. for 7 h, and then calcine at 650° C. for 3 h to obtain an adsorbent precursor;

[0078] (3) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S2; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 350°C, reduction treatment time 4 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 90%;

[0079] Among them, the first metal component (zinc + nickel) and the second metal component (cobalt) are both calculated as oxides, the mass of the first metal component accounts for 60% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 3% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (cobalt oxide) accounts for 0.4% of the sum of the masses of the carrier and the first metal component.

[0080] Example 3

[0081] (1) 52 g of small-pore SB powder, 156 g of potassium-modified macroporous pseudo-boehmite I, 42 g of silicon oxide, 50 g of sesbania powder, 700 g of zinc oxide powder, and 167 g of nickel acetate tetrahydrate were mixed uniformly, 480 g of water and 41.6 g of nitric acid were added thereto, and after mixing uniformly, the mixture was squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 36 hours, then dried at 110° C. for 6 hours, and then calcined at 500° C. for 5 hours to obtain a small ball intermediate;

[0082] (2) Weighing 14.1 g of copper nitrate, adding 2000 g of water thereto to prepare a first impregnation solution, placing the intermediate in the first impregnation solution, and impregnating at 55° C. for 10 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 90° C. for 8 h, and then calcining at 650° C. for 3 h to obtain an adsorbent precursor;

[0083] (3) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S3; wherein the reduction treatment conditions are: pressure 0.5 MPa, temperature 450°C, reduction treatment time 2 h, hydrogen volume space velocity 1500 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 100%;

[0084] Among them, the first metal component (zinc + nickel) and the second metal component (copper) are both calculated as oxides, the mass of the first metal component accounts for 75% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 5% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (copper oxide) accounts for 0.6% of the sum of the masses of the carrier and the first metal component.

[0085] Example 4

[0086] (1) 46 g of small-pore SB powder, 185 g of potassium-modified macroporous pseudo-boehmite II, 69 g of silicon oxide, 40 g of sesbania powder, 600 g of zinc oxide powder, and 289 g of nickel nitrate hexahydrate were mixed uniformly, 530 g of water and 69.3 g of nitric acid were added thereto, and after mixing uniformly, the mixture was squeezed into small balls with a particle diameter of 2 mm. The small balls were naturally dried at room temperature for 24 hours, then dried at 90° C. for 8 hours, and then calcined at 500° C. for 4 hours to obtain a small ball intermediate;

[0087] (2) Weighing 19.5 g of cobalt nitrate (on a dry basis, excluding crystal water), adding 2900 g of water thereto to prepare a first impregnation solution, placing the intermediate in the first impregnation solution, and impregnating at 40° C. for 12 h; drying the obtained impregnation product at room temperature for 20 h, then drying at 100° C. for 10 h, and then calcining at 550° C. for 3 h to obtain an adsorbent precursor;

[0088] (3) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S4; wherein the reduction treatment conditions are: pressure 0.5 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the hydrogen-containing atmosphere is 70%;

[0089] Among them, the first metal component (zinc + nickel) and the second metal component (cobalt) are both calculated as oxides, the mass of the first metal component accounts for 69.2% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 7.62% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (cobalt oxide) accounts for 0.82% of the sum of the masses of the carrier and the first metal component.

[0090] Example 5

[0091] (1) 60 g of small-pore SB powder, 209 g of potassium-modified macroporous pseudo-boehmite II, 81 g of silicon oxide, 30 g of sesbania powder, 570 g of zinc oxide powder, and 266 g of nickel acetate tetrahydrate were mixed uniformly, 460 g of water and 107 g of nitric acid were added thereto, and after mixing uniformly, the mixture was squeezed into small balls with a particle diameter of 2 mm, and the small balls were naturally dried at room temperature for 12 hours; then dried at 100° C. for 10 hours, and then calcined at 450° C. for 4 hours to obtain a small ball intermediate;

[0092] (2) Weighing 16.5 g of copper nitrate, adding 2000 g of water thereto to prepare a first impregnation solution, placing the intermediate in the first impregnation solution, and impregnating at 45° C. for 12 h; drying the obtained impregnation product at room temperature for 18 h, then drying at 110° C. for 6 h, and then calcining at 600° C. for 4 h to obtain an adsorbent precursor;

[0093] (3) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S1; wherein the reduction treatment conditions are: pressure 1 MPa, temperature 400°C, reduction treatment time 3 h, hydrogen volume space velocity 3000 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 60%;

[0094] Among them, the first metal component (zinc + nickel) and the second metal component (copper) are both calculated as oxides, the mass of the first metal component accounts for 65% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 8% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (copper oxide) accounts for 0.7% of the sum of the masses of the carrier and the first metal component.

[0095] Example 6

[0096] (1) 56 g of small-pore SB powder, 194 g of potassium-modified macroporous pseudo-boehmite II, 50 g of silicon oxide, 30 g of sesbania powder, 620 g of zinc oxide powder, and 311 g of nickel nitrate hexahydrate were mixed uniformly, 450 g of water and 75 g of nitric acid were added thereto, and after mixing uniformly, small balls with a particle diameter of 2 mm were squeezed out, and the small balls were naturally dried at room temperature for 18 hours, then dried at 80° C. for 9 hours, and then calcined at 550° C. for 3 hours to obtain a small ball intermediate;

[0097] (2) Weighing 14.7 g of cobalt nitrate (on a dry basis, excluding crystal water), adding 2500 g of water thereto to prepare a first impregnation solution, placing the intermediate in the first impregnation solution, and impregnating at 60° C. for 8 h; drying the obtained impregnation product at room temperature for 24 h, then drying at 110° C. for 8 h, and then calcining at 650° C. for 3 h to obtain an adsorbent precursor;

[0098] (3) The adsorbent precursor is subjected to reduction treatment in an atmosphere containing hydrogen to obtain a spherical desulfurization adsorbent S1; wherein the reduction treatment conditions are: pressure 1.5 MPa, temperature 350°C, reduction treatment time 4 h, hydrogen volume space velocity 2500 h -1 , the volume fraction of hydrogen in the atmosphere containing hydrogen is 80%;

[0099] Among them, the first metal component (zinc + nickel) and the second metal component (cobalt) are both calculated as oxides, the mass of the first metal component accounts for 70% of the sum of the masses of the carrier and the first metal component, the mass of nickel in the first metal component accounts for 8% of the sum of the masses of the carrier and the first metal component, and the mass of the second metal component (cobalt oxide) accounts for 0.6% of the sum of the masses of the carrier and the first metal component.

[0100] Comparative Example 1 to Comparative Example 6

[0101] The difference between Comparative Example 1 and Example 4 is that the potassium-modified macroporous pseudo-boehmite is replaced by a macroporous pseudo-boehmite raw material that has not been modified with potassium (i.e., the potassium modification treatment of the macroporous pseudo-boehmite raw material is cancelled), and the other conditions are the same as those in Example 4, to obtain a desulfurization adsorbent D1.

[0102] The difference between Comparative Example 2 and Example 4 is that the small-pore SB powder in step (1) is replaced by potassium-modified large-pore pseudo-boehmite II, and the other conditions are the same as those in Example 4 to obtain a desulfurization adsorbent D2.

[0103] The difference between Comparative Example 3 and Example 4 is that the potassium-modified macroporous pseudo-boehmite in step (1) is replaced by small-pore pseudo-boehmite (the pore volume of the small-pore pseudo-boehmite is 0.4 mL / g to 0.6 mL / g and the specific surface area is 180 m 2 / g~260m 2 / g), and the other conditions were the same as those in Example 4 to prepare desulfurization adsorbent D3.

[0104] The difference between Comparative Example 4 and Example 4 is that the silicon oxide in step (1) is replaced by potassium-modified macroporous pseudo-boehmite II, and the other conditions are the same as those in Example 4, to obtain a desulfurization adsorbent D4.

[0105] The difference between Comparative Example 5 and Example 5 is that the silicon oxide in step (1) is replaced by small-pore SB powder, and the other conditions are the same as those in Example 5, to obtain a desulfurization adsorbent D5.

[0106] The difference between Comparative Example 6 and Example 5 is that the potassium-modified macroporous pseudo-boehmite in step (1) is replaced by a macroporous pseudo-boehmite raw material that has not been modified with potassium (i.e., the potassium modification treatment of the macroporous pseudo-boehmite raw material is cancelled), and the other conditions are the same as in Example 5, to obtain a desulfurization adsorbent D6.

[0107] Application Examples

[0108] The desulfurization process of this application example is as follows: 200g of adsorbent is loaded into a fixed bed reactor, and then a heavy oil raw material is introduced into the fixed bed reactor, and is contacted and reacted with the desulfurization adsorbent under a hydrogen atmosphere (i.e., a desulfurization reaction is performed), and a desulfurized oil product and a regenerated adsorbent are obtained respectively; wherein the heavy oil raw material is a vacuum residue oil with a sulfur content of 2.8wt%, and the conditions of the desulfurization process are: a temperature of 420°C, a pressure of 4MPa, a feed rate of the heavy oil raw material of 100g / h (the feed space velocity of the heavy oil raw material is 0.5h -1 ), hydrogen flow rate 35L / h (the volume ratio of hydrogen to heavy oil feedstock is 400:1).

[0109] S1-S6 and D1-D6 were used as desulfurization adsorbents to carry out the above desulfurization process, so as to evaluate the performance of S1-S6 and D1-D6. The crushing strength of adsorbents S1-S6 and D1-D6 and the desulfurization rate achieved by each adsorbent are shown in Table 1 and Table 2, respectively.

[0110] Table 1 Desulfurization adsorbent performance evaluation results

[0111] Desulfurization adsorbent S1 S2 S3 S4 S5 S6 Crushing strength / N 41 46 42 45 44 43 Desulfurization rate / % 84 80 82 83 85 82

[0112] Table 2 Desulfurization adsorbent performance evaluation results

[0113] Desulfurization adsorbent D1 D2 D3 D4 D5 D6 Crushing strength / N 39 14 18 38 35 32 Desulfurization rate / % 76 82 68 74 77 73

[0114] It can be seen from Table 1 and Table 2 that, compared with D1-D6, S1-S6 have both good mechanical properties and desulfurization activity.

[0115] It is also found that the sulfur capacity of S1-S6 is significantly higher than that of D1-D6, showing excellent sulfur storage and sulfur adsorption capabilities. To more intuitively show the difference, S3-S6, D1, and D6 are taken as examples, and their sulfur capacities are shown in Table 3.

[0116] The sulfur capacity (adsorbent breakthrough sulfur capacity) Sc is calculated at the node when the desulfurization rate is 80%, and the calculation formula is as follows: Sc = Q × ρ (C0-C1) × t × 10 -6 / m×100%, Sc is the sulfur penetration capacity of the adsorbent; Q is the flow rate of the heavy oil feedstock, in mL / h; ρ is the density of the heavy oil feedstock, in g·cm -3 ; C0 is the sulfur content of the heavy oil feedstock, in mg / kg; C1 is the sulfur content of the desulfurized oil product output from the reactor outlet, in mg / kg; t is the desulfurization time, in h; m is the mass of the adsorbent, in g.

[0117] Table 3 Desulfurization adsorbent performance evaluation results

[0118] Desulfurization adsorbent S3 S4 S5 S6 D1 D6 Sulfur capacity of desulfurization adsorbent Sc / % 7.7 7.9 7.6 7.8 5.2 5.0

[0119] In addition, the adsorbent stability of S1~S6 and D1~D6 was evaluated, and the desulfurization activity of the adsorbent after different regeneration times was measured. The results showed that the desulfurization activity stability of S1~S6 was much better than that of D1~D6. Specifically, the desulfurization rate of the adsorbent after different regeneration times was measured according to the following desulfurization-regeneration process:

[0120] The above desulfurization process is carried out using unused fresh adsorbent to obtain desulfurized oil products and primary adsorbent, and the desulfurization rate of the fresh adsorbent is measured;

[0121] The regenerated adsorbent is regenerated according to the following regeneration process: the regenerated adsorbent is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 5%, and the volume space velocity of the oxygen-containing gas is 2500h -1 The temperature of the oxidation regeneration is 400°C, the pressure of the oxidation regeneration is 0.4 MPa, and the time of the oxidation regeneration is 75 h; the regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain a regenerated adsorbent (i.e., regenerated once); wherein the hydrogen volume fraction in the hydrogen-containing atmosphere is 80%, and the volume space velocity of hydrogen is 3000 h -1 , the temperature of the second reduction treatment is 350°C, the pressure of the second reduction treatment is 1.2MPa, and the time of the second reduction treatment is 3h;

[0122] The above desulfurization process is carried out using a single-regenerated adsorbent to obtain a desulfurized oil product and a secondary adsorbent to be regenerated, and the desulfurization rate of the single-regenerated adsorbent is measured; the secondary adsorbent to be regenerated is then regenerated according to the above regeneration process to obtain a secondary regenerated adsorbent (i.e., regenerated twice); the above desulfurization process is carried out using a secondary regenerated adsorbent to obtain a desulfurized oil product and a secondary adsorbent to be regenerated, and the desulfurization rate of the secondary regenerated adsorbent is measured… According to the above process, the desulfurization rates after the adsorbent is regenerated 1, 4, 7, 10, 13, 16, 19, 22, 25, 28, 32, and 35 times are measured respectively.

[0123] Taking S4, S5, D4 and D5 as examples, the desulfurization rates corresponding to different regeneration times measured according to the above process are shown in Table 4.

[0124] Table 4 Adsorbent stability evaluation results

[0125]

[0126] Note: After D4 and D5 were regenerated 13 times, the desulfurization rate dropped significantly and was not shown in Table 4.

[0127] It can be seen from Table 4 that after S4 and S5 were regenerated 35 times, they were still able to maintain a high desulfurization rate, which was basically equivalent to that of fresh desulfurization adsorbent, showing good desulfurization activity stability.

[0128] In addition, in order to further illustrate the performance difference between the desulfurization adsorbent prepared in the above embodiment and the desulfurization adsorbent prepared in the comparative example, taking S1, S2, D4, and D5 as examples, XRD analysis was performed on the adsorbent precursor in the preparation process (i.e., the product before the first reduction treatment) and the regenerated adsorbent precursor when the fifth regeneration was performed according to the above desulfurization-regeneration process (i.e., the product before the second reduction treatment), and the results are shown in FIG. Figure 1 and Figure 2 ,in, Figure 1 The fresh agent S1 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent S1, the fresh agent S2 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent S2, the fresh agent D4 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent D4, and the fresh agent D5 is the adsorbent precursor in the preparation process of the fresh desulfurization adsorbent D5; Figure 2 The regeneration agent S1 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent S1 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent S2 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent S2 is regenerated for the fifth time according to the above desulfurization-regeneration process, the regeneration agent D4 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent D4 is regenerated for the fifth time according to the above desulfurization-regeneration process, and the regeneration agent D5 is a regeneration adsorbent precursor when the fresh desulfurization adsorbent D5 is regenerated for the fifth time according to the above desulfurization-regeneration process.

[0129] from Figure 1 and Figure 2It can be seen that the main characteristic diffraction peaks in fresh agent S1, fresh agent S2, fresh agent D4 and fresh agent D5 are zinc oxide crystal phase peaks (2θ is 31.5°, 34.4° and 36.2°) and nickel oxide crystal phase peaks (2θ is 36.9° and 43.0°). The characteristic diffraction peak of ZnO is sharp and has high intensity, and it is the main active component. Compared with the fresh agent, the XRD spectra of the regenerated agent (i.e., regenerated agent S1, regenerated agent S2, regenerated agent D4 and regenerated agent D5) are Figure 2 ) is significantly more complex, in which, in addition to regeneration products such as ZnO and NiO, new phases such as desulfurization products ZnS and ZnAl2O4 are generated. Compared with regeneration agents S1, S2, D4 and D5, the intensity of the characteristic diffraction peak of zinc-aluminum spinel is significantly enhanced in the XRD spectra.

[0130] The active ZnO in the desulfurization adsorbent continuously reacts with the aluminum source in the carrier to generate inactive zinc-aluminum spinel, and the zinc-aluminum spinel can no longer be converted into active ZnO during the regeneration process, indicating that it is difficult to regenerate, thereby forming an inactive component, and due to its high content, it will cause the content of the active component ZnO in the desulfurization adsorbent to be greatly reduced, thereby causing problems such as difficulty in sulfur transfer during adsorption desulfurization, affecting the desulfurization activity and other properties of the desulfurization adsorbent; at the same time, the formation of zinc-aluminum spinel will also destroy the carrier structure, resulting in a decrease in the strength of the desulfurization adsorbent, making the desulfurization adsorbent more easily broken and deteriorating its performance. Therefore, the above XRD analysis further illustrates that the desulfurization adsorbent prepared by the embodiment has better desulfurization activity stability and mechanical strength and other properties than the desulfurization adsorbent prepared by the comparative example.

[0131] The above describes the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A desulfurization adsorbent, characterized in that: The invention comprises a carrier, a first metal component and a second metal component, wherein the carrier is compounded from raw materials including small-pore SB powder, silicon oxide and potassium-modified macroporous pseudo-boehmite, wherein the pore volume of the small-pore SB powder is not greater than 0.6 mL / g, and the pore volume of the potassium-modified macroporous pseudo-boehmite is not less than 0.8 mL / g; the first metal component comprises zinc and nickel, and the second metal component comprises cobalt and / or copper; Calculated based on the oxide of the first metal component and the oxide of the second metal component, the following conditions are satisfied: The mass of the first metal component accounts for 60% to 80% of the sum of the mass of the carrier and the first metal component; and / or, The mass of nickel in the first metal component accounts for 3% to 13% of the sum of the mass of the support and the first metal component; and / or, The mass of the second metal component accounts for 0.4% to 1% of the sum of the mass of the carrier and the first metal component; The pore volume of the small-pore SB powder is 0.4 mL / g to 0.6 mL / g, and the specific surface area is 180 m 2 / g~260m 2 / g, the peptization index is greater than 98%; and / or, The potassium-modified macroporous pseudo-boehmite has a pore volume of 0.8 mL / g to 1.2 mL / g and a specific surface area of ​​280 m 2 / g~360m 2 / g.

2. The desulfurization adsorbent according to claim 1, characterized in that: The mass ratio of the small-pore SB powder to the potassium-modified large-pore pseudo-boehmite is 1:(2-5); and / or, The ratio of the mass of the silicon oxide to the sum of the mass of the potassium-modified macroporous pseudo-boehmite and the microporous SB powder is (0.1-0.4):

1.

3. The desulfurization adsorbent according to claim 1, characterized in that The potassium-modified macroporous pseudo-boehmite is prepared according to a process comprising the following steps: a pseudo-boehmite raw material is impregnated with a second impregnation solution containing a potassium compound, and the pseudo-boehmite is obtained after drying and roasting; wherein the mass ratio of the second impregnation solution to the pseudo-boehmite raw material is (2-5):1; the potassium compound comprises at least one of potassium nitrate, potassium carbonate, potassium sulfate and potassium chloride; the mass ratio of the potassium compound to the pseudo-boehmite raw material is (0.05-0.3):1 in terms of potassium oxide; the drying temperature is 80°C-120°C, and the roasting temperature is 450°C-550°C.

4. The method for preparing the desulfurization adsorbent according to any one of claims 1 to 3, characterized in that: include: (I) adding an inorganic acid and water to a mixture containing potassium-modified macroporous pseudo-boehmite, microporous SB powder, silicon oxide, a binder, zinc oxide, and a nickel compound, and then sequentially forming, drying, and calcining to obtain an intermediate; (II) impregnating the intermediate with a first impregnation solution containing a compound of a second metal component, and drying and calcining the impregnation product to obtain an adsorbent precursor; (III) subjecting the adsorbent precursor to a first reduction treatment in an atmosphere containing hydrogen to obtain the desulfurization adsorbent.

5. The preparation method according to claim 4, characterized in that: The binder comprises at least one of methyl cellulose, sodium carboxymethyl starch and sesbania powder; and / or, The nickel compound is calculated as nickel oxide, and the mass of the binder accounts for 2% to 6% of the sum of the mass of the potassium-modified macroporous pseudo-boehmite, microporous SB powder, silicon oxide, zinc oxide and the nickel compound; and / or, The zinc oxide comprises nano zinc oxide powder having a particle size not greater than 100 nm; and / or, The ratio of the mass of the inorganic acid to the sum of the mass of the potassium-modified macroporous pseudo-boehmite and the microporous SB powder is (0.1-0.5):1; and / or, The calcination conditions in step (I) are: calcination temperature of 400° C. to 700° C., calcination time of 1 h to 10 h; and / or, The calcination conditions in step (II) are: calcination temperature of 400° C. to 700° C., calcination time of 1 h to 10 h; and / or, In step (III), the volume space velocity of hydrogen is 500h -1 ~4000h -1 The temperature of the first reduction treatment process is 300°C to 500°C, the pressure of the first reduction treatment process is 0 to 3MPa, and the time of the first reduction treatment is 1h to 6h.

6. A method for desulfurization of sulfur-containing oil by adsorption, characterized in that: include: Desulfurization of sulfur-containing oil products using the desulfurization adsorbent according to any one of claims 1 to 3; or, The desulfurization adsorbent is prepared according to the preparation method of claim 4 or 5, and the desulfurization treatment of sulfur-containing oil is carried out using the prepared desulfurization adsorbent.

7. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: The temperature of the desulfurization treatment is 300°C to 550°C; and / or, The desulfurization treatment pressure is 0.5MPa to 10MPa; and / or, The feed space velocity of the sulfur-containing oil is 0.1h -1 ~1.0h -1 and / or, The desulfurization treatment is carried out in a hydrogen atmosphere, and the volume ratio of the hydrogen to the sulfur-containing oil is (100-800):

1.

8. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: Also includes: After the desulfurization treatment, desulfurized oil products and adsorbent to be produced are obtained respectively; Regenerating the adsorbent to be regenerated to obtain a regenerated adsorbent; The regenerated adsorbent is returned to the desulfurization process; wherein the regeneration process comprises: The regenerated adsorbent is oxidized and regenerated in the presence of an oxygen-containing gas to obtain a regenerated adsorbent precursor; wherein the volume fraction of oxygen in the oxygen-containing gas is 1% to 10%, and the volume space velocity of the oxygen-containing gas is 1000h -1 ~3000h -1 , the temperature of the oxidation regeneration is 300°C to 500°C, the pressure of the oxidation regeneration is 0 to 0.5MPa, and the time of the oxidation regeneration is 20h to 100h; The regenerated adsorbent precursor is subjected to a second reduction treatment in an atmosphere containing hydrogen to obtain the regenerated adsorbent; wherein the volume space velocity of the hydrogen is 500h -1 ~4000h -1 The temperature of the second reduction treatment is 300° C. to 500° C., the pressure of the second reduction treatment is 0 to 3 MPa, and the time of the second reduction treatment is 1 h to 6 h.

9. The method for desulfurization of sulfur-containing oil by adsorption according to claim 6, characterized in that: The sulfur component in the sulfur-containing oil product includes at least one of carbon oxysulfide, carbon disulfide, mercaptans, hydrogen sulfide, and thiophene compounds, and the thiophene compounds include at least one of benzothiophene, dibenzothiophene, benzonaphthiophene, alkylbenzothiophene, alkyldibenzothiophene, and alkylbenzonaphthiophene; and / or, the sulfur-containing oil product includes heavy oil, and the heavy oil includes at least one of wax oil, atmospheric residue oil, and vacuum residue oil.

Citation Information

Patent Citations

  • Preparation method of modified activated carbon adsorption desulfurizing agent

    CN101804325A

  • High-selectivity gasoline desulfurization adsorbent as well as preparation method and application thereof

    CN104028208A

  • High-selectivity gasoline adsorption desulfurizer as well as preparation method and application thereof

    CN104028217A

  • Desulfurization catalyst, preparation method thereof and hydrocarbon oil desulfurizing method

    CN104511286A

  • Adsorption desulfurization additive, as well as preparation method and desulfurization system thereof

    CN104549131A